ANALYSIS OF THE TOURISM SECTOR CONTRIBUTION TO THE IMPROVEMENT ECONOMIC GROWTH IN CENTRAL JAVA - Hillary Netty Habsari; Dame Esther Mastina Hutabarat (Journal of Applied Economics in Developing Countries, 2023)
This research  aims to determine the effect of the degree of number of tourists, the number of tourist attractions, hotel occupancy rates, and the average length of stay of tourists on economic growth using the parameters of the Gross Regional Domestic Product. This research was conducted on all regencies or cities in Central Java Province with a total of 35 regencies or in the period 2009-2018. The data source used in this study is secondary data taken from the Central Statistics Agency page and the Youth, Sports, and Tourism Office which are then further processed. The data analysis method used is multiple linear regression test using panel data. The results of the study showed that the number of tourists, the number of tourist attractions, and the average length of stay of each tourist had a positive and significant impact on Gross Regional Domestic Product, while hotel room occupancy rates did not have any effect on Gross Regional Domestic Product. In addition to the number of tourists, the number of tourist attractions, hotel room occupancy rates, and the average length of stay of tourists simultaneously or together have a significant effect on Gross Regional Domestic Product. From this research it can be concluded that the tourism sector is able to make a major contribution to economic growth.